RESTORATIVE JUSTICE ASPECT IN STRENGTHENING PRELIMINARY EVIDENCE AUDIT IN INDONESIAN TAXATION - Denny Irawan (Scientia Integritas Utama, 2022)
Challenges and problems of justice in handling tax crime cases must be handled by implementing restorative justice in examining preliminary evidence in the field of taxation. This has also been confirmed in the National Medium-Term Development Plan (RPJMN) 2020-2024, which emphasizes that the improvement of the legal system must be realized through one crucial strategy, namely the application of Restorative Justice. Based on a study using a normative juridical method that can answer problem-identification and provide suggestions, this paper produces two conclusions. First, the principle of restorative justice is still very adequate to be adopted in the rules for examining preliminary evidence, as regulated in Number 18/PMK.03/2021, which has amended several provisions in PMK Number 239/PMK.03/2014. Secondly, restorative justice provisions in strengthening preliminary evidence examinations should be based on the following two essential keys. First, preventing tax avoidance and tax evasion is carried out through efforts to obtain consistent benefits rather than punishment. Second, preliminary evidence is examined if tax avoidance and tax evasion have occurred and if efforts are needed to recover state revenue losses from the sector through solutions and support for the state as a victim of active state participation and taxpayers. Thus, producing rules for examining preliminary evidence that reflect the fulfillment of material requirements, formal requirements, and restorative justice mechanisms.